The Effect of Consumer Credit, Performance Allowances, Work Discipline, and Work Environment on The Performance of Civil Servants in Ternate City - Junet Thenu; R. Bambang Budhijana (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2026)
This study aims to analyze the influence of Consumptive Credit, Performance Allowance, Work Discipline, and Work Environment on the Performance of Civil Servants (PNS) in Ternate City. Using a quantitative approach with 102 respondents through purposive sampling and PLS-SEM analysis assisted by SmartPLS 4.1.1.6. The results indicate that consumptive credit, work discipline, and work environment have a positive and significant effect on civil servant performance. In contrast, performance allowance shows no significant effect, indicating that the incentive system has not been functioning effectively. This study recommends merit-based allowance reform as well as strengthening discipline and work environment to improve the quality of regional bureaucracy.